Use of social communication networks for the promotion and empowerment of women's health: experience report (Research, Society and Development, 2020)
Health education is characterized as a simple device for community intervention and empowerment, reducing social vulnerabilities. This paper aims to demonstrate the use of social communication networks for the promotion and empowerment of women's health. In this sense, a page on the social media Instagram was developed by nursing students, entitled “enf.saudemulher”. In order to promote health education focused on women's empowerment, addressing topics such as: gynecology, pharmacology, pathology, family planning, obstetrics, among other free topics. They are weekly topics chosen by the followers themselves through the interest of the majority. In the designated place for posts, easy-to-understand phrases and an association image are placed. The “@ enf.saudemulher” page has 630 followers, the majority of whom are 93% women, aged between 13 - 54 years, with a larger scale in the age group of 18 - 24 years in the city of Crateús - Ceará. Each theme has a didactic image that is easy to understand, created by the academics themselves, so some followers use the message location to forward a personal report with some personal experiences. It was concluded that the guidelines using the means of communication as a form of health education, establish a link between the population and professionals, enabling prevention, promotion, self-knowledge and quality of life for the population. Thus, using technological means to promote health, allows the population to develop confidence in the knowledge offered by nursing students.